Low incidence of primary biliary cirrhosis (PBC) in the first‐degree relatives of PBC probands after 8 years of follow‐up. (28th April 2016) - Gulamhusein, Aliya F.; Juran, Brian D.; Atkinson, Elizabeth J.; McCauley, Bryan; Schlicht, Erik; Lazaridis, Konstantinos N.
Abstract: Background & Aims: Primary biliary cirrhosis (PBC) is characterized by chronic cholestasis and disease‐specific antimitochondrial antibodies (AMA). A high prevalence of AMAs in first‐degree relatives (FDRs) of PBC probands has been reported, although the natural history of such patients has not been described. We aimed to assess the risk of developing PBC in AMA+ FDRs of patients with PBC. Methods: First‐degree relatives recruited to the Mayo Clinic PBC Genetic Epidemiology Registry and Biorepository were followed for disease onset after recruitment. Development of PBC was ascertained via self‐report during a telephone interview and/or via proband report on a questionnaire. Chi‐squared test and t ‐test were used to assess the differences between categorical and continuous variables respectively. A mixed‐effects model was used to assess the change in biochemical profiles over time. Results: Forty AMA+ and 423 AMA− subjects were included and followed for a median of 8.9 and 8.4 years respectively. Overall, 3% ( n = 15) of FDRs were diagnosed with PBC, and AMA+ FDRs had a higher risk than AMA− FDRs (24% vs. 0.7%, P < 0.01). However, among undiagnosed FDRs, only 4% of AMA+ ( n = 1) and 0.4% of AMA− ( n = 1) FDRs were diagnosed with PBC ( P = 0.17) during the follow‐up period. None of the AMA+ FDRs with normal alkaline phosphatase at baseline developed PBC in follow‐up. Conclusions: Our results suggest a low risk of developing PBC over time in FDRs of patients with PBC, particularly those without biochemical evidence of cholestasis at baseline. These data are useful in counselling and reassuring relatives of their overall favourable prognosis.